1981
DOI: 10.1007/bf01978802
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, insect sterilizing and ovicidal activity of some cobalt(II) and cobalt(III) complexes

Abstract: Twenty-one mixed-ligand complexes of cobalt(II) and cobalt(III) have been screened for their antimicrobial, insect sterilizing and ovicidal activities. Three of these cobalt(III) complexes exhibit broad antimicrobial spectra, including against human bacterial pathogens, dermatophytes and plant pathogenic fungi, while one exhibits feeble activity against a human pathogenic bacterium. These results have been compared with the activity of the corresponding cobalt(II) complexes, which have been found to be inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…(1) the release of Co 2+ ions, similar to silver and copper compounds and (2) the direct interaction between the Co 2+ with the microbial cellular membrane [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…(1) the release of Co 2+ ions, similar to silver and copper compounds and (2) the direct interaction between the Co 2+ with the microbial cellular membrane [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Co 2+ is a known inhibitor of ethylene synthesis (Lau and Yang, 1976); therefore, it was suggested that the positive effect of Co(NO 3 ) 2 was related to a wound reaction mediated by ethylene. However, Co 2+ as Co(NO 3 ) 2 is also known to have antibacterial properties (Dey et al, 1981). Further experiments carried out with Adiantum raddianum fronds by Van Doorn et al (1991a) established that ethylene did not trigger vascular blockage in cut fronds.…”
Section: Cobaltmentioning
confidence: 96%
“…Three replica were performed for each test. A distribution test was performed to obtain the statistical significance of the data [1] (Tables 4-6).…”
Section: Test Proceduresmentioning
confidence: 99%
“…In continuation of our work on the antimicrobial, insect sterilization and ovicidal activity of metallic complexes [1], we have studied the action of some oxo-vanadium(IV) and oxovanadium(V) complexes in these respects.…”
Section: Introductionmentioning
confidence: 99%